THE ROLE OF PERCEPTION CELEBRITY ENDORSER AGAINST LIVE-STREAM SHOPPING INTENTIONS SALES OF FISHERY PRODUCTS - Bhiaztika Ristyanadi; Fuquh Rahmat Shaleh; Luluk Nur Azizah (Jurnal Ekonomi, 2023)
The development of people's need for a product occurs in today's modern era. Every organization or company that produces a product and sells it to consumers must do various ways so that the products it sells can attract consumers' interest so that consumers are interested in buying it. This encourages market players to think creatively and market their products. Product marketing that is most often done is to create product advertisements. The attractiveness of the advertisement itself is important. One that is chosen by marketers to increase the attractiveness of advertising is to use a public figure to convey the message of their product advertisement. Marketing in this way is also known as a celebrity endorser. The purpose of this study was to determine the effect of using a celebrity as a messenger for advertising messages on advertising attractiveness and purchase intention. The object of this research is fishery products. The sample for this research was female students at the Islamic University of Lamongan who had purchased fishery products. Data collection techniques were carried out using a questionnaire. The analysis tool used is SPSS. The results of this study indicate that celebrity endorser has a significant positive effect on Live-Stream attractiveness, and Live-Stream attractiveness has a significant positive effect on Shopping Intentions.